Clinical Management of Adrenal Tumors - Lew, John I. (IntechOpen, 2017)
This book presents an overview of adrenal tumors written by a multidisciplinary team of world experts who provide comprehensive, evidence-based perspective of their topics in this field and current approaches to the management of adrenal tumors. The areas discussed in this book include an overview of adrenal incidentalomas, unusual presentations of adrenal tumors, genetic basis of pheochromocytomas and paragangliomas, pathophysiology, and medical and surgical treatment and approaches to patients with benign and malignant adrenal tumors. Each chapter written by these experts provides clinical evidence, treatment recommendations, and algorithms. Clinical Management of Adrenal Tumors will serve as a valuable resource of current information regarding adrenal tumors for medical students, residents in training, physicians, and researchers.